2023
DOI: 10.1002/slct.202302669
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Characterization and In Vitro Cell Cytotoxicity of ZnO Nanoparticles on MDA‐MB 231 Breast Cancer Cell Line

Ashok Kumar Janakiraman,
Zi Yin Wong,
Zenli Cheng
et al.

Abstract: The intention of this study was to prepare zinc oxide nanoparticles (ZnO‐NPs) via bottom‐up approach and evaluate their physiochemical, antimicrobial and anticancer properties. ZnO‐NPs were first prepared by the direct precipitation method with zinc sulphate heptahydrate, followed by characterization tests using sophisticated analytical and imaging instruments. Upon characterization, ZnO‐NPs were studied for their antimicrobial activities against Staphylococcus aureus, Staphylococcus epidermidis and Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Also, the spreadability, viscosity, and pH of LoR-NS gel were stable in the same experimental conditions. The data obtained with LoR-NS suspension corroborate previously published data 38 . There was no significant difference ( p > 0.05) in stability after 2 months, and the slight changes observed in its pH, %CDR, viscosity and % EE but not significantly difference after 90 days as given in Table 5 and Fig.…”
Section: Resultssupporting
confidence: 90%
“…Also, the spreadability, viscosity, and pH of LoR-NS gel were stable in the same experimental conditions. The data obtained with LoR-NS suspension corroborate previously published data 38 . There was no significant difference ( p > 0.05) in stability after 2 months, and the slight changes observed in its pH, %CDR, viscosity and % EE but not significantly difference after 90 days as given in Table 5 and Fig.…”
Section: Resultssupporting
confidence: 90%
“…The findings of our study were confirmed by Ramya et al, 5 who documented significant cytotoxicity at lower doses when utilizing biological TiO 2 NPs, owing to their fascinating attributes. Prior studies have consistently shown that ZnO nanoparticles can induce harm to a range of cell types, including the human MDA‐MB 231 Breast Cancer Cell Lines, SW480 Cell Lines, A549 cancer cells, and MG‐63 cells Ashokkumar et al, 30 Marjan et al, 31 Tamil Elakiya et al, 23 and Jun et al 32 …”
Section: Resultsmentioning
confidence: 99%